2020
DOI: 10.1002/hbm.25259
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory fitness, hippocampal subfield volumes, and mnemonic discrimination task performance in aging

Abstract: Aging and exercise have opposing effects on mnemonic discrimination task performance, which putatively taxes pattern separation mechanisms reliant on the dentate gyrus (DG) subfield of the hippocampus. In young adults, increasing cardiorespiratory fitness (CRF) has been shown to improve mnemonic discrimination task performance and increase left anterior DG/CA3 volume. It is unknown how these variables interact in cognitive aging, yet this knowledge is critical, given the established effects of aging on hippoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 119 publications
1
33
0
Order By: Relevance
“…In addition, Frodl et al (2019) and Nauer et al (2020) found that middle aged and young adults had increased CA4/DG and DG/CA3 volumes to various PA interventions. A common characteristic to these three different results is the use of PA interventions in contrast with the passive measurements of daily PA in Kern et al (2021) and Varma et al (2015). A possible explanation is that PA interventions could have acute effects in some structures, while the daily PA, assessed through VO 2 max, measured daily walking activity and questionnaires, may have another nature of changes that are reflected in the subiculum.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, Frodl et al (2019) and Nauer et al (2020) found that middle aged and young adults had increased CA4/DG and DG/CA3 volumes to various PA interventions. A common characteristic to these three different results is the use of PA interventions in contrast with the passive measurements of daily PA in Kern et al (2021) and Varma et al (2015). A possible explanation is that PA interventions could have acute effects in some structures, while the daily PA, assessed through VO 2 max, measured daily walking activity and questionnaires, may have another nature of changes that are reflected in the subiculum.…”
Section: Discussionmentioning
confidence: 99%
“…To sum up, previous research on PA had shown that PA produces changes in the structure and function of the hippocampus (K. Erickson & Kramer, 2009; A. Thomas et al, 2012;Tao et al, 2016;Ikuta et al, 2019;Esteban-Cornejo et al, 2021;Voss, Erickson, et al, 2010;Boraxbekk et al, 2016;Kern et al, 2021) but had barely addressed whether…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, our study was the first to directly examine the interaction between gender and exercise on mnemonic discrimination performance, and to report this gender difference (favoring females) in self-reported exercise effects on spatial pattern separation. Prior studies examining mnemonic discrimination and exercise or cardiorespiratory fitness have either controlled for gender as a covariate in the analyses (Bernstein & McNally, 2019; Bullock et al., 2018; Heisz et al., 2017; Kern et al., 2021; Nauer, Schon, et al., 2020; Nauer, Dunne, et al., 2020; Maass et al., 2015; Suwabe, Hyodo, Byun, Ochi, Fukuie, et al., 2017), or did not analyze gender separately (Chaire et al., 2020; Dèry et al., 2013; Kovacevic et al., 2020; Suwabe, Hyodo, Byun, Ochi, Yassa, et al., 2017; Suwabe et al., 2018), perhaps due to limitations in participant sample sizes. In fact, sex differences in exercise effects on cognition have largely been underexplored, especially with regard to memory function (Loprinzi & Frith, 2018).…”
Section: Discussionmentioning
confidence: 99%